Monoterpene Indole Alkaloids with Cav3.1 T-Type Calcium Channel Inhibitory Activity from Catharanthus roseus - Zhen-Tao Deng (MDPI AG, 2021)
Catharanthus roseus is a well-known traditional herbal medicine for the treatment of cancer, hypertension, scald, and sore in China. Phytochemical investigation on the twigs and leaves of this species led to the isolation of two new monoterpene indole alkaloids, catharanosines A (1) and B (2), and six known analogues (3–8). Structures of 1 and 2 were established by 1H-, 13C- and 2D-NMR, and HREIMS data. The absolute configuration of 1 was confirmed by single-crystal X-ray diffraction analysis. Compound 2 represented an unprecedented aspidosperma-type alkaloid with a 2-piperidinyl moiety at C-10. Compounds 6–8 exhibited remarkable Cav3.1 low voltage-gated calcium channel (LVGCC) inhibitory activity with IC50 values of 11.83 ± 1.02, 14.3 ± 1.20, and 14.54 ± 0.99 μM, respectively.